Confirmatory factor analysis of the irrational Performance Beliefs Inventory (iPBI) in a sample of amateur and semi-professional athletes. (March 2018) - Turner, M.J.; Allen, M.S.
Abstract: Objectives: This investigation sought to test the construct validity of the irrational performance beliefs inventory (iPBI) in a sample of amateur and semi-professional athletes. Method: In total, 550 athletes (312 men, 212 women, M age  = 38.04 ± 13.80 years) completed the iPBI and demographic questions at a single time point. Results: Confirmatory factor analysis showed lower than acceptable fit indices for the 28-item iPBI (comparative fit index [CFI] = 0.84). After removal of potential problem items, a 20-item version (iPBI-2) was developed (CFI = 0.91). Results showed that amateur athletes scored higher than semi-professional athletes on primary irrational beliefs and low frustration tolerance, whereas semi-professional athletes scored higher than amateur athletes on depreciation. Conclusions: This study provides initial evidence of construct validity for a 20-item version of the iPBI in an athletic sample, and shows medium effect size differences in irrational beliefs between amateur and semi-professional athletes. Highlights: CFA showed lower than acceptable fit indices for 28-item iPBI. A 20-item version (iPBI-2) was developed and tested. The iPBI-2 demonstrated acceptable fit indices. The iPBI-2 demonstrated comparable concurrent validity to the 28-item iPBI. Differences in irrational beliefs between sexes and athlete levels also emerged.